2017
DOI: 10.1021/acschembio.7b00282
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Remodeling of Human Erythropoietin (EPO) Through Combined Mammalian Cell Engineering and Chemoenzymatic Transglycosylation

Abstract: The tremendous structural heterogeneity of N-glycosylation of glycoproteins poses a great challenge for deciphering the biological functions of specific glycoforms and for developing protein-based therapeutics. We have previously reported a chemoenzymatic glycan remodeling method for producing homogeneous glycoforms of N-glycoproteins including intact antibodies, which consist of endoglycosidase-catalyzed deglycosylation and novel glycosynthase-catalyzed transglycosylation, but its application to complex glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Therefore the high mannose type is an ideal substrate for Endo-H digestion, leaving a terminal GlcNac at the asparagine residue at each N-glycosylation site. An engineered glycosynthase based on Endo-M (EndoM-N175A) is known to be able to transfer N-glycans, including sialylated biantennary complex types based on an oxazoline derivate to a single GlcNAc residue 33 . For a further improvement of the glycan transfer to the GlcNAc residues a second acceptor substrate composed of a core focusylated EPO glycoform was investigated (Fucα1,6GlcNAc-EPO).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the high mannose type is an ideal substrate for Endo-H digestion, leaving a terminal GlcNac at the asparagine residue at each N-glycosylation site. An engineered glycosynthase based on Endo-M (EndoM-N175A) is known to be able to transfer N-glycans, including sialylated biantennary complex types based on an oxazoline derivate to a single GlcNAc residue 33 . For a further improvement of the glycan transfer to the GlcNAc residues a second acceptor substrate composed of a core focusylated EPO glycoform was investigated (Fucα1,6GlcNAc-EPO).…”
Section: Discussionmentioning
confidence: 99%
“…The mutant was capable of synthesizing asialo biantennary and complex triantennary core-fucosylated glycoforms of rituximab (intact antibody) in yields over 95%. Further applications, indicating the high potential of the method for the synthesis of pharmaceutical relevant compounds were the chemoenzymatic production of vaccine candidates [ 72 ]; the site-selective glycosylation of HIV-1 polypeptide antigen bearing two different glycans (yields up to 95%) [ 73 ]; the glycan remodeling of human erythropoietin (EPO) [ 74 ]; and the synthesis of mannose-6-phosphate-containing glycoproteins [ 75 ]. Tang et al impressively demonstrated a one-pot N -glycan remodeling of IgG proteins by combining the wild type ( wt ) Endo-M glycosidase with the synthase variant Endo-S D322S [ 76 ].…”
Section: Glycoside Syntheses Using Glycosynthase Methodsmentioning
confidence: 99%
“…Consequently, in vitro glycan remodeling was developed to offer the advantage of adding customized oligosaccharides on recombinant proteins to produce a single uniform glycoform [ 26 , 38 , 39 ]. In particular, using the endoglycosidase-catalyzed glycan remodeling approach, N-linked glycoproteins are enzymatically deglycosylated such that the innermost GlcNAc or Fucα-1,6GlcNAc remains on the asparagine residue of the protein [ 40 , 41 , 42 , 43 ]. This approach allows for an N -glycan oxazoline substrate to be transferred en bloc onto that remaining GlcNAc of recombinant proteins to reconstitute homogeneous glycoproteins.…”
Section: Introductionmentioning
confidence: 99%